Toward a Transformative Multicultural Pedagogy: The Role of Cultural Empathy in University - Andri Fransiskus Gultom (Actual Insight, 2025)
In the context of increasing global diversity, universities are challenged to implement educational paradigms that not only acknowledge cultural plurality but also foster meaningful intercultural understanding. This research offers a novel contribution to the field by articulating cultural empathy not merely as an affective disposition but as a transformative pedagogical praxis with structural implications. While existing literature often treats multiculturalism as a policy framework, this study investigates its operationalization through the lens of empathy-based engagement within a university setting. Utilizing a qualitative approach at Universitas PGRI Kanjuruhan Malang, data were analyzed through the Miles and Huberman interactive model. Findings reveal that multicultural education is integrated through a shared ethos of human dignity, formal curriculum embedding, and institutionalized policy commitments. Furthermore, five dimensions of empathy-based pedagogy emerge: content integration, collaborative knowledge construction, experiential prejudice reduction, equitable educational relationships, and cultural empowerment through embodied expressions like culinary arts and dance. By shifting the paradigm from surface-level diversity management to deep intercultural competency, these results provide a replicable framework for global higher education institutions. Ultimately, the study advocates for reorienting multicultural pedagogy toward transformative frameworks that institutionalize empathy as a critical competency for social justice.